Assessing the Physical Comfort of Musallas in Urban Parks: A Case Study of Taman Flora and Taman Prestasi in Surabaya - Hapsari, Oktavi Elok (Universitas Islam Negeri Sunan Ampel Surabaya, 2022)
This study investigates the physical comfort of musallas (prayer chambers) in two urban parks in Surabaya: Taman Flora and Taman Prestasi. The study examines the impact of natural ventilation, strategic positioning of openings, and thermal comfort on creating a favorable prayer environment in tropical climes. The study demonstrates that the musallas in both parks effectively employ natural air circulation, as evidenced by field observations and analysis of ventilation criteria. Furthermore, these musallas comply with national comfort guidelines (SNI). In addition, the design takes into account the need for gender-segregated places and includes amenities such as mukena to accommodate cultural and religious rituals, hence improving the overall user experience. The results emphasize the significance of incorporating deliberate design features in public areas to guarantee comfort and ease of use, providing useful knowledge for upcoming urban park projects.